ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, CAPITAL) (STUDI PADA PT BANK CENTRAL ASIA, TBK. PERIODE 2009-2018) - Laras Sati Giri Noerani; Nila Firdausi Nuzula (Jurnal Administrasi Bisnis, 2020)
Bank soundness level analysis is an analysis technique which is employed to determine the financial condition and management of the bank. The purpose of the analysis using the RGEC method is to determine the soundness of a bank, where the health of a bank is a competency carried out by banks to be able to carry out their activities by applicable regulations. This analysis is carried out using ratios by Bank Indonesia Regulation No.13/1/PBI/2011 which in its assessment uses the RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) approach. The subject of this study was PT Bank Central Asia, Tbk. This study used descriptive approach. The data were obtained from various reports published by PT Bank Central Asia, Tbk. both from the official website of PT Bank Central Asia, Tbk. (www.bca.co.id) and the Indonesia Stock Exchange (www.idx.co.id). The data collection methods would be in the form of studying, classifying and using secondary data related to the object of research. The data analysis technique would be conducted by analyzing the focus of RGEC research and then drawn conclusions from the finished calculations to determine the bank soundness level in accordance with Bank Indonesia Regulations.Keywords: Bank Soundness level, RGEC Method